Respostas
respondido por:
0
g)
4x+6-2x=x-6+10+14
4x-2x-x=-6+10+14-6
x=12
h)
3(5-x)-3(1-2x)=42
15-3x-3+6x=42
3x=42+3-15
x=30/3
x=10
i )
3x+2x=15
5x=15
x=3
j)
2x+4x=12
6x=12
x=2
4x+6-2x=x-6+10+14
4x-2x-x=-6+10+14-6
x=12
h)
3(5-x)-3(1-2x)=42
15-3x-3+6x=42
3x=42+3-15
x=30/3
x=10
i )
3x+2x=15
5x=15
x=3
j)
2x+4x=12
6x=12
x=2
respondido por:
0
i) 5x=15
x=15/3
x=5
j) 6x=12, o seis ta dividindo passa a multiplicar
x=12/6, logo x= 2
x=15/3
x=5
j) 6x=12, o seis ta dividindo passa a multiplicar
x=12/6, logo x= 2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás